The Effect of Corporate Social Responsibility, Family Ownership on Tax Avoidance: The Effect of Audit Quality Moderation - Santi Yopie; Elivia Elivia (Indonesian Journal of Economics, Social, and Humanities, 2022)
Large tax receipts are essential for every country for its growth and development but it’s constrained by the fact that some people are not willing to pay taxes voluntarily and deliberately avoid tax in various ways. This research aims to examine the effect of corporate social responsibility, family ownership and audit quality on tax avoidance. This research also investigates whether audit quality can affect the causal relation of family ownership to tax avoidance. This research was conducted using non-financial firms. Total of sample that have met all the criteria was 158 companies which was registered on the Indonesia Stock Exchange (IDX) in the period of 2015-2019. Data obtained were tested with panel regression. Regression analysis results reveal that corporate social responsibility and tax avoidance are positively associated, corporation with high corporate social responsibility disclosure are less likely to engage in tax avoidance. Family ownership, on the other hand, affects tax avoidance negatively which means that family firms engage in more tax avoidance than non-family firms. Audit quality has a significant positive effect on tax avoidance but does not affect the relationship of family ownership to tax avoidance.